Occlusal recording components for dental implant-supported prostheses. - A Monzavi; M Alikhasi; F Taghavi (Tehran University of Medical Sciences, 2012)
In this article, three techniques for maxillo-mandibular relationship for Replace-Select implants are described. The use of healing abutments, planning abutments, and Impression copings are presented, and the advantages and disadvantages are discussed.